2017
DOI: 10.1364/ol.42.002455
|View full text |Cite
|
Sign up to set email alerts
|

Simple statistical channel model for weak temperature-induced turbulence in underwater wireless optical communication systems

Abstract: In this Letter, we use laser beam intensity fluctuation measurements to model and describe the statistical properties of weak temperature-induced turbulence in underwater wireless optical communication (UWOC) channels. UWOC channels with temperature gradients are modeled by the generalized gamma distribution (GGD) with an excellent goodness of fit to the measured data under all channel conditions. Meanwhile, thermally uniform channels are perfectly described by the simple gamma distribution which is a special … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 125 publications
(83 citation statements)
references
References 16 publications
1
77
0
Order By: Relevance
“…Besides, optimal combining schemes and maximum likelihood detection schemes were investigated in 2012. 153) Additionally, the effects of turbulence and geometries of the system on the received signal energy distribution were studied by Liao et al 154) For UWOC, UV scattering enhanced by water molecules, dissolved organic matters and ions makes it feasible to construct underwater UV NLOS communications, which may mitigate the alignment problems caused by turbulence, such as in the presence of bubbles, 45) the gradient of salinity and temperature, 46) in a UWOC with LOS. An underwater NLOS network concept was proposed by means of backreflection at the ocean-air interface and a corresponding mathematical model was derived.…”
Section: Los and Nlos Communicationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Besides, optimal combining schemes and maximum likelihood detection schemes were investigated in 2012. 153) Additionally, the effects of turbulence and geometries of the system on the received signal energy distribution were studied by Liao et al 154) For UWOC, UV scattering enhanced by water molecules, dissolved organic matters and ions makes it feasible to construct underwater UV NLOS communications, which may mitigate the alignment problems caused by turbulence, such as in the presence of bubbles, 45) the gradient of salinity and temperature, 46) in a UWOC with LOS. An underwater NLOS network concept was proposed by means of backreflection at the ocean-air interface and a corresponding mathematical model was derived.…”
Section: Los and Nlos Communicationsmentioning
confidence: 99%
“…The impact of temperature gradient was experimentally investigated in Ref. 46. Similar to salinity gradient, it was found that the log-normal distribution, traditionally used in atmospheric optical turbulent channels, failed to mimic the statistical behavior of the measured irradiance.…”
Section: 3mentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, it has also its own challenges and is still in its infancy. Underwater absorption, scattering, and turbulence are the key factors that significantly affect the performance of UWOC links and image-quality of underwater video and imaging systems [5]- [7]. As a matter of fact, only short range links have been established for UWOC [8]- [12].…”
Section: Introductionmentioning
confidence: 99%